Human Monocyte-Derived Dendritic Cells Produce Millimolar Concentrations of ROS in Phagosomes Per Second - Paardekooper, Laurent M.; Dingjan, Ilse; Linders, Peter T. A.; Staal, Alexander H. J.; Cristescu, Simona M.; Verberk, Wilco C. E. P.; van den Bogaart, Geert (Frontiers in Immunology, 2019)
Neutrophils kill ingested pathogens by the so-called oxidative burst, where reactive oxygen species (ROS) are produced in the lumen of phagosomes at very high rates (mM/sec), although these rates can only be maintained for a short period (minutes). In contrast, dendritic cells produce ROS at much lower rates, but they can sustain production for much longer after pathogen uptake (hours). It is becoming increasingly clear that this slow but prolonged ROS production is essential for antigen cross-presentation to activate cytolytic T cells and shapes the repertoire of antigen fragments for presentation to helper T cells. However, despite this importance of ROS production by dendritic cells for activation of the adaptive immune system, their actual ROS production rates have never been quantified. Here, we quantified ROS production in human monocyte-derived dendritic cells by measuring the oxygen consumption rate during phagocytosis. Although a large variation in oxygen consumption and phagocytic capacity was present among individuals and cells, we estimate a ROS production rate of on average ~0.5 mM/second per phagosome. Quantitative microscopy approaches showed that ROS is produced within minutes after pathogen encounter at the nascent phagocytic cup. H2DCFDA measurements revealed that ROS production is sustained for at least ~10 hours after uptake. While ROS are produced by dendritic cells at an about 10-fold lower rate than by neutrophils, the net total ROS production is approximately similar. These are the first quantitative estimates of ROS production by a cell capable of antigen cross-presentation. Our findings provide a quantitative insight in how ROS affect dendritic cell function.